2013
DOI: 10.5194/se-4-153-2013
|View full text |Cite
|
Sign up to set email alerts
|

Spatial models for monitoring the spatio-temporal evolution of ashes after fire – a case study of a burnt grassland in Lithuania

Abstract: Abstract. Ash thickness is a key variable in the protection of soil against erosion agents after planned and unplanned fires. Ash thickness measurements were conducted along two transects (flat and sloping areas) following a grided experimental design. In order to interpolate data with accuracy and identify the techniques with the least bias, several interpolation methods were tested in the grided plot. Overall, the fire had a low severity. However, the fire significantly reduced the ground cover, especially o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 50 publications
3
60
0
1
Order By: Relevance
“…A heterogeneous pattern of soil protection is obtained after fire, which varies with compaction and redistribution of ash. This means that soil is differentially exposed to erosion agents and other processes (Pérez-Cabello et al, 2012;Pereira et al, 2013b). The thickness of the ash layer depends on fire severity: thin ash layers are observed after low-severity fire, while thick ash layers are observed after highseverity fire due to the consumption of larger amounts of fuel.…”
Section: Ashmentioning
confidence: 99%
See 3 more Smart Citations
“…A heterogeneous pattern of soil protection is obtained after fire, which varies with compaction and redistribution of ash. This means that soil is differentially exposed to erosion agents and other processes (Pérez-Cabello et al, 2012;Pereira et al, 2013b). The thickness of the ash layer depends on fire severity: thin ash layers are observed after low-severity fire, while thick ash layers are observed after highseverity fire due to the consumption of larger amounts of fuel.…”
Section: Ashmentioning
confidence: 99%
“…Studies carried out by Pereira et al (2013aPereira et al ( , 2013b in Lithuania show that the greatest loss occurred in the first days after fire, as a result of rainfall. They also found that loss of ash was more important in high-severity burned areas, and was caused by erosion and compaction ash layer (Pereira et al, 2013b). In Mediterranean areas, a significant ash layer has been observed during periods ranging between a few days (Cerdà and Doerr, 2008;Zavala et al, 2009) …”
Section: Ashmentioning
confidence: 99%
See 2 more Smart Citations
“…Incomplete fuel combustion produces black ash (Úbeda et al, 2009), especially in low-severity fires, as in the present one, where the temperatures do not reach high values (Keeterings and Bigham, 2000). Normally, black ash is incorporated into the soil or can be eroded in the weeks following the fire (Pereira et al, 2013b), contributing to the darkening of the soil following the fire and the reduction of Munsell value as observed in this study and in previous reports (Ulery and Relative frequency of SWR for composite and sieved soil fractions, (a) unburned, after the fire; (b) burned, after the fire; (c) unburned, 2 months after the fire; (d) burned, 2 months after the fire; (e) unburned, 5 months after the fire; (f) burned, 5 months after the fire; (g) unburned, 7 months after the fire; (h) burned, 7 months after the fire; (i) unburned, 9 months after the fire; and (j) burned, 9 months after the fire. Graham, 1991).…”
Section: Soil Munsell Colour Valuementioning
confidence: 99%